INDONESIA`S ROLE IN THE ISSUE OF HUMAN RIGHT VIOLATIONS AGAINST THE UIGHUR ETHNIC GROUP IN XINJIANG - Merliana, Merri; Rachmat, Angga Nurdin; Oktaviani, Jusmalia (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2024)
The issue of human rights violations against the Uighur ethnic group in Xinjiang, China, has drawn attention from Western countries as promoters of human rights and Muslim-majority nations, within the framework of solidarity. For Indonesia, the issue of human rights violations against the Uighur ethnic group poses a dilemma. This dilemma stems from Indonesia's status as a member of the UN Human Rights Council for the 2020-2022 period and as a country with a Muslim-majority population, while China, accused of committing human rights violations against the Uighur ethnic group, is a strategic economic partner. Based on this context, this paper aims to discuss the question of Indonesia's role in the issue of human rights violations against the Uighur ethnic group in the years 2020-2022. The purpose of this paper is to describe and analyze Indonesia's role using K.J. Holsti's theory of national roles, based on identity and interests from a constructivist perspective. The paper finds that Indonesia plays three roles in the issue of human rights violations against the Uighur ethnic group: independent, example, and bridge. These roles are based on Indonesia's identity as a middle power country with economic interests and its identity as a member of the UN Human Rights Council.